2017
DOI: 10.1016/j.ica.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Increased photocatalytic activity in Ru(II),Rh(III) supramolecular bimetallic complexes with terminal ligand substitution

Abstract: a b s t r a c tThree new Ru(II),Rh(III) supramolecular bimetallic complexes of the design [(Ph 2 phen) 2 Ru(dpp)RhCl 2 (R 2 -bpy)](PF 6 ) 3 (R = CH 3 (Ru-Rh(Me 2 bpy)), H (Ru-Rh(bpy)), or COOCH 3 (Ru-Rh(dmeb)); Ph 2 phen = 4, 7-diphenyl-1,10-phenanthroline; dpp = 2,3-bis(2-pyridyl)pyrazine; dmeb = 4,4 0 -dimethyl ester-2,2 0 -bipyridine; bpy = 2,2 0 -bipyridine; Me 2 bpy = 4,4 0 -dimethyl-2,2 0 -bipyridine) have been synthesized and analyzed to determine the impact that the polypyridyl terminal ligand (TL) coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…There is a debate considering the reaction of Rh­(I) with proton. Some groups reported that Rh­(I) reacts with a proton to produce the corresponding hydride species (Rh–H). , ,, However, recently, several groups reported that a Rh complex with η 4 -pentamethylcyclopentadiene (Cp*H) as a ligand forms in the presence of weak acid in organic solvents. Since the Rh–H species was not identified in the in situ UV–visible spectra under the present photocatalytic reaction conditions, we cannot determine the structure of the Rh–H species. In the CV of Ru–Rh in DMA-TEOA (4:1 v/v) under CO 2 (red line in Figure ), catalytic current was observed at a potential similar to that of the first one-electron reduction wave of the Ru unit ( E 1/2 = −1.74 V).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…There is a debate considering the reaction of Rh­(I) with proton. Some groups reported that Rh­(I) reacts with a proton to produce the corresponding hydride species (Rh–H). , ,, However, recently, several groups reported that a Rh complex with η 4 -pentamethylcyclopentadiene (Cp*H) as a ligand forms in the presence of weak acid in organic solvents. Since the Rh–H species was not identified in the in situ UV–visible spectra under the present photocatalytic reaction conditions, we cannot determine the structure of the Rh–H species. In the CV of Ru–Rh in DMA-TEOA (4:1 v/v) under CO 2 (red line in Figure ), catalytic current was observed at a potential similar to that of the first one-electron reduction wave of the Ru unit ( E 1/2 = −1.74 V).…”
Section: Resultsmentioning
confidence: 76%
“…Several homogeneous photocatalytic systems have been reported for the selective formation of HCOOH from CO 2 , such as oligo­( p -phenylenes), a mixed system of phenazine and Co-cyclam, a mixed system with [Ru­(bpy) 2 (CO) 2 ] 2+ (bpy = 2,2′-bipyridine) as a catalyst and [Ru­(bpy) 3 ] 2+ as a photosensitizer, and as supramolecular photocatalysts containing Ru-catalyst and Ru-photosensitizer (PS) units . By contrast, Rh complexes have been reported as efficient H 2 evolution catalysts in various photocatalytic systems, though there is no report regarding a photochemical system using a Rh-complex catalyst for CO 2 reduction. This study reports on the first supramolecular photocatalyst consisting of [Rh­(BL)­(Cp*)­Cl] + as a catalyst with [Ru­(dmb) 2 (BL)] 2+ as a photosensitizer unit ( Ru–Rh : BL = 1,2-bis­(4′-methyl­[2,2′-bipyridin]-4-yl)­ethane, Cp* = 1,2,3,4,5-pentamethylcyclopentadienyl, dmb = 4,4′-dimethyl-2,2′-bipyridine) (Figure ) for CO 2 reduction giving HCOOH as the main product, whereas the mixed system using the corresponding mononuclear complexes, such as [Rh­(dmb)­(Cp*)­Cl] + ( Rh ) and [Ru­(dmb) 3 ] 2+ ( Ru ), produces H 2 as the main product.…”
Section: Introductionmentioning
confidence: 99%
“…Not long ago, in 2017, three Ru( ii )–Rh( iii ) dimetallic complexes were presented: [Ru(Ph 2 phen) 2 (dpp)RhCl 2 (4,4′-R-bpy)](PF 6 ) 3 (R = Me ( 1 ), H ( 2 ), COOMe ( 3 )); Ph 2 phen = 4,7-diphenyl-1,1′-phenanthroline; dpp = 2,3-bis(2-pyridyl)pyrazine; bpy = 2,2′-bipyridine (Scheme 1). 42 The evaluation of their properties as photocatalysts for hydrogen production showed that their activity is correlated with the bipyridine-σ-donating ability and the rate of Rh–Cl dissociation upon electrochemical reduction. Despite their similarity, complex 3 , containing the weaker σ-donating dmeb (dmeb = 4,4′-dimethyl ester-2,2′-bipyridine) ligand and showing the highest rate constant for chloride dissociation, generated the largest amount of H 2 from water in the presence of N , N -dimethylaniline as the electron donor, its maximum quantum yield ( Φ H 2 max ) being 0.004 after 4 h under photolysis (Table 1).…”
Section: Experimental and Theoretical Studiesmentioning
confidence: 99%
“…These components include the PS, CAT, and the molecu-lar bridging unit B [4][5][6][7][8] that chemically links PS and CAT. Notably, complexes of Ni(II), [9] Co(II), [10][11][12] Rh(III), [13][14][15][16] Pd(II), [17][18][19] Pt(II) [4,20] or polyoxometalates [21] as CAT, as well as transition metal complexes [11,22,23] and organic dyes [24,25] as PS have demonstrated success in light-driven catalysis in respective PS-B-CAT systems. To date, intramolecular photocatalysts including a Ru(II) polypyridyl complex as the PS are the most intensively studied systems.…”
Section: Introductionmentioning
confidence: 99%